REVIEW AN HISTORIOGRAPHICAL STUDY OF ARRIAN'S ANABASIS Daniel W. Leon, Arrian the Historian: Writing the Greek Past in the Roman Empire. Austin: University of Texas Press, 2021. Pp. xii + 180. Hardback, 50.00. ISBN 978-1-4773-2186-7. Issue 16 (2022) - Baron, Christopher
No abstract available